Combination of platelet to lymphocyte ratio and neutrophil to lymphocyte ratio is a useful prognostic factor in advanced non‐small cell lung cancer patients. Issue 3 (May 2015) - Wu, Guannan; Yao, Yanwen; Bai, Cuiqing; Zeng, Junli; Shi, Donghong; Gu, Xiaoling; Shi, Xuefei; Song, Yong
Abstract: Background: The neutrophil to lymphocyte ratio (NLR) was recently shown to be a remarkable prognostic factor in tumors. Moreover, some studies have indicated that the combination of NLR and platelet to lymphocyte ratio (PLR) could be a better prognostic factor. As the combined prognostic value of NLR and PLR in non‐small cell lung cancer (NSCLC) is not clear, we conducted this study to explore this further. Methods: A total of 366 primary NSCLC patients with stage III or IV were finally included. The neutrophil, platelet, and lymphocyte counts were recorded before treatment was initiated. NLR and PLR were calculated and NLR > 2.68 or PLR > 119.50 was defined as elevated. Univariate and multivariate survival analyses were conducted to test their prognostic value. Results: The median of NLR and PLR were 3.14 and 152.63, respectively, in all patients. It was indicated that PLR is linearly associated with NLR. PLR is associated with survival, but is not an independent prognostic factor. Removing NLR, PLR is an independent prognostic factor (overall survival [OS]: hazard ratio [HR] = 1.918, P = 0.003; progression‐free survival [PFS]: HR = 1.822, P = 0.007 in condition of NLR ≤ 2.68). It was also indicated that elevated NLR is an independent prognostic factor (OS: HR = 1.778, P = 0.009; PFS: HR = 1.535, P = 0.022) in all patients. Conclusions: PLR is a useful complement of NLR, thus, advanced NSCLC patients could be divided into three prognostic groups prior to treatment: poor: NLR > 2.68; moderate: NLR ≤ 2.68 and PLR > 119.50; and good: NLR ≤ 2.68 and PLR ≤ 119.50.